2015
DOI: 10.1016/j.wear.2015.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of laser cladding as an option for repairing/enhancing rails

Abstract: This paper presents results of testing carried out to assess the wear and RCF performance of laser clad rail. Stronger and harder materials can be laser clad on top of the working surfaces of standard (e.g. 260 grade) rail in order to improve wear and RCF life. A twin-disc method has been used to assess the suitability of various candidate cladding materials. The materials were clad on top of 260 grade rail discs and were tested against a disc of standard wheel material. Wear was measured by weighing the discs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(58 citation statements)
references
References 13 publications
(17 reference statements)
0
58
0
Order By: Relevance
“…It was therefore decided to test both materials in this work to see if there were any tribological benefits to using Stellite 12 over Stellite 6. This work follows on from previous tests [1] where much shorter duration wear tests were performed. Results of previous wear testing were found to be inconclusive and it was decided that the short test duration had not been enough to show steady state wear of the samples.…”
Section: R260mentioning
confidence: 97%
See 1 more Smart Citation
“…It was therefore decided to test both materials in this work to see if there were any tribological benefits to using Stellite 12 over Stellite 6. This work follows on from previous tests [1] where much shorter duration wear tests were performed. Results of previous wear testing were found to be inconclusive and it was decided that the short test duration had not been enough to show steady state wear of the samples.…”
Section: R260mentioning
confidence: 97%
“…Stellite 6 was tested in [1] and was found to show superior wear and RCF resistance. The microstructure of Stellite 12 is thought to promote greater RCF resistance over Stellite 6.…”
Section: R260mentioning
confidence: 99%
“…Beyond comparison of crack growth predictions with the physical evidence for existing rail defects (Figure 1), validation depends on identifying such a material, and developing a crack growth law specific to mixed mode non-inclined sub-surface cracks. When considering new rail coating technologies [19] there is also the possibility of choosing a coating with this crack suppressing property. Even if contraction cannot be achieved, there would be benefit in selecting steel metallurgy able to reduce levels of expansion when metallurgical transformation takes place following thermal input.…”
Section: Microstructure Designmentioning
confidence: 99%
“…With the fast development of laser cladding technology, more and more attention has been paid to the repairing area and has been developed rapidly [15][16][17][18]. Lewis et al [19] used four different powders to improve the wear and rolling contact fatigue (RCF) life of rails by laser cladding. The results showed that the wear resistance of rails was improved and the RCF life was increased by laser cladding.…”
Section: Introductionmentioning
confidence: 99%